2007
DOI: 10.1016/j.aquabot.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors that control Typha marsh evapotranspiration

Abstract: There is continuing debate about the controls on wetland evapotranspiration (E t ) and whether marshes are profligate water users. We used eddy covariance to measure the CO 2 exchange and E t by a California Tule marsh in 2003. The marsh was dominated by Typha and Scirpus, and there was a large amount of standing litter that acted as a mulch. Canopy development was broadly related to air temperature, with rapid growth in May and senescence in October. E t was a few tenths of a mm d À1 in winter, and 3-4 mm d À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 37 publications
5
81
1
2
Order By: Relevance
“…At the same time, due to the high costs of measuring instruments, and also because of various technical factors affecting the quality of the data obtained, a number of studies devoted to the measurement of evapotranspiration present the results of measurement experiments lasting for several weeks or seasons. They mainly present the daily patterns of water vapour flux or the daily totals of evapotranspiration against the background of meteorological conditions (Souch et al 1998;Kurbatova et al 2002;Gasca-Tucker et al 2007), as well as the results of impact assessment of parameters such as foliage surface area or surface resistance on the rate of evapotranspiration (Acreman et al 2003;Gulden et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, due to the high costs of measuring instruments, and also because of various technical factors affecting the quality of the data obtained, a number of studies devoted to the measurement of evapotranspiration present the results of measurement experiments lasting for several weeks or seasons. They mainly present the daily patterns of water vapour flux or the daily totals of evapotranspiration against the background of meteorological conditions (Souch et al 1998;Kurbatova et al 2002;Gasca-Tucker et al 2007), as well as the results of impact assessment of parameters such as foliage surface area or surface resistance on the rate of evapotranspiration (Acreman et al 2003;Gulden et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The SJFM is located near the campus of the University of California at Irvine, at 3 m above sea level and 8 km northeast of the Pacific Ocean (Goulden et al, 2007). The SJFM is part of the University of California's Natural Reserve System.…”
mentioning
confidence: 99%
“…5, but this pattern was observed in each of the 31 years that were modelled. Further research of the transpiration patterns of vegetation that formed the reed collar around the (Carter, 1996;Holt et al 1998;Goulden et al, 2007 andZhou andZhou, 2009), as well as testing, showed significantly better results were obtained when no evaporation losses were assigned to the reed collar in the winter months (Fig. 6).…”
Section: Water Balancementioning
confidence: 96%